2016
DOI: 10.1021/jacs.6b06320
|View full text |Cite
|
Sign up to set email alerts
|

Unreacted PbI2 as a Double-Edged Sword for Enhancing the Performance of Perovskite Solar Cells

Abstract: Lead halide perovskites have over the past few years attracted considerable interest as photo absorbers in PV applications with record efficiencies now reaching 22%. It has recently been found that not only the composition but also the precise stoichiometry is important for the device performance. Recent reports have, for example, demonstrated small amount of PbI2 in the perovskite films to be beneficial for the overall performance of both the standard perovskite, CH3NH3PbI3, as well as for the mixed perovskit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

65
745
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 765 publications
(831 citation statements)
references
References 84 publications
65
745
3
Order By: Relevance
“…Our findings are, in principle, also applicable to mixed cation/halide systems as these films are also deposited from non-stoichiometric mixtures. [34] In this case we expect a similar effect upon exposure to moisture as the typical cations used, formamidinium and cesium, are also hygroscopic and will likely undergo a similar enhanced mobility in the presence of water.…”
Section: Introductionmentioning
confidence: 83%
“…Our findings are, in principle, also applicable to mixed cation/halide systems as these films are also deposited from non-stoichiometric mixtures. [34] In this case we expect a similar effect upon exposure to moisture as the typical cations used, formamidinium and cesium, are also hygroscopic and will likely undergo a similar enhanced mobility in the presence of water.…”
Section: Introductionmentioning
confidence: 83%
“…The better gain performance in these perovskites with a deficiency of lead is in contrast to perovskite solar cells, where a lead excess was found to improve the efficiency [37,38]. Jacobsson et al recently suggested that a lead excess is improving charge carrier transport through grain boundaries while the overall crystal quality suffers, however, with a net positive effect for solar cells [38]. Since charge carrier transport is less important in our optically pumped devices, the better crystal quality together with the smoother surface can explain the lower ASE thresholds.…”
Section: Ase Thresholds and Stabilitymentioning
confidence: 93%
“…Next, we investigated the role of the stoichiometric ratio between lead to the sum of all cations, since recent investigations have revealed a large influence of this parameter on the efficiency of solar cells [37,38]. The lead to cation ratio (Pb/A) is defined as the ratio of the number of lead (Pb) anions divided by the sum of the three A cations (number of MA molecules + number of FA molecules + number of Cs cations) in the precursor solution.…”
Section: Ase Thresholds and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 However, it is challenging to obtain highly crystalline perovskite films with full surface coverage using this procedure. 19 Thus, several modifications including solvent engineering, 20 fast deposition-crystallization 21 and the addition of different additives [22][23][24][25][26] have been developed. These complex preparation methods are sensitive to small changes in the precursors composition and thus reproducibility remains an issue for improving MAPbI 3 films 24 towards the highest performing multication perovskites.…”
Section: Introductionmentioning
confidence: 99%